2017
DOI: 10.3389/fpsyg.2017.01164
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary Knowledge Predicts Lexical Processing: Evidence from a Group of Participants with Diverse Educational Backgrounds

Abstract: Vocabulary knowledge is central to a speaker's command of their language. In previous research, greater vocabulary knowledge has been associated with advantages in language processing. In this study, we examined the relationship between individual differences in vocabulary and language processing performance more closely by (i) using a battery of vocabulary tests instead of just one test, and (ii) testing not only university students (Experiment 1) but young adults from a broader range of educational backgroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 40 publications
(97 reference statements)
6
61
0
Order By: Relevance
“…This is in line with earlier research showing a clear link between vocabulary knowledge and performance in all four language skills (Milton, 2013). It is also in line with the finding that various vocabulary tests measure the same skill (Mainz, Shao, Brysbaert & Meyer, 2017). It confirms the importance of vocabulary in language learning, especially at early levels (starting from absolute beginners).…”
Section: Discussionsupporting
confidence: 88%
“…This is in line with earlier research showing a clear link between vocabulary knowledge and performance in all four language skills (Milton, 2013). It is also in line with the finding that various vocabulary tests measure the same skill (Mainz, Shao, Brysbaert & Meyer, 2017). It confirms the importance of vocabulary in language learning, especially at early levels (starting from absolute beginners).…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, it is plausible that average RTs reflect a collection of wordspecific processing speeds (hereafter, the emergent capacity account). This approach captures the fact that many item-level features of words predict speed of lexical access (e.g., frequency, imageability, age of acquisition), which in some cases interacts with vocabulary knowledge (e.g., Mainz, Shao, Brysbaert, & Meyer, 2017). An emergent capacity account is consistent with domain-specific theoretical approaches to automization, where increased experience with specific events automatizes (i.e., speeds up) processing (e.g., Logan, 1988).…”
Section: The Nature Of Individual Differences In Lexical Processing Ementioning
confidence: 71%
“…Finally, earlier studies have shown that participants' vocabulary size predicted performance in picture-naming and lexical-decision tasks, with larger vocabularies being associated with faster and/or more accurate responses (see Brysbaert, Stevens, Mandera, & Keuleers, 2016;Diependaele, Lemhöfer, & Brysbaert, 2013;Mainz, Shao, Brysbaert, & Meyer, 2017). In addition, some studies have reported weaker word frequency effects in participants with larger, compared to smaller, vocabularies (Brysbaert, Lagrou, & Stevens, 2017;Diependaele et al, 2013;Yap, Tse, & Balota, 2009).…”
Section: The Choice Of Linguistic and Nonlinguistic Tasksmentioning
confidence: 96%